Efektivitas Indikator Alami Mengandung Antosianin Dalam Mendeteksi Cemaran Boraks Pada Makanan - Ratih Lukmitarani; Arna Rosyada; Asep Tata Gunawan; Bunga Nuur Primayu Utami (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
Degenerative diseases constitute a major public health challenge in Indonesia. Consumer health is severely compromised when food products are contaminated with chemical contaminants. However, community-level initiatives for detecting borax adulteration in food remain poorly implemented. Therefore, there is a critical need to develop alternative borax detection tools utilizing natural, anthocyanin-rich indicators. This study aimed to determine the most effective natural anthocyanin-based extract for detecting borax contamination in food samples. The research employed a pre-experimental method utilizing a Static Group Comparison design. The test samples consisted of lontong (rice cakes), artificially adulterated with 3 grams of borax per 100 grams of rice per portion to ensure sample homogeneity. The proportions of borax and rice were standardized as a laboratory simulation. The natural indicators used are derived from natural materials containing anthocyanins specifically mangosteen peel, sappanwood, dragon fruit peel, and purple sweet potato in the form of extracts. These extracts were prepared using the maceration extraction technique. The results demonstrated that the detection efficacy for borax in the samples was highest using the sappan wood extract (83.3%), followed by dragon fruit peel (66.6%), and both mangosteen pericarp and purple sweet potato (50.0%). Statistical analysis utilizing the Fisher's Exact test yielded a p-value of 0.141, indicating no statistically significant difference in detection efficacy between the four natural indicators and the commercial borax test kit. In conclusion, while the variance in effectiveness among the natural indicators lacks statistical significance, their practical detection capabilities are comparable to, and as reliable as, the standard reference test kit. Consequently, the public and food industry stakeholders can utilize these natural indicators, particularly sappan wood, as a cost-effective and highly accessible tool for borax detection.